Carrier based liquid bioformulation of salt-tolerant PGPR Bacillus species for prolonged survivability - Chompa, Sayma Serine; Ali Tan, Kee Zuan; Mohd Amin, Adibah; Tan, Geok Hun; Ahmad Ghazali, Amir Hamzah; Sadeq, Buraq Musa; Akter, Amaily; Rahman, Md Ekhlasur; Rashid, Harun Ur; Nabayi, Abba (Penerbit Universiti Kebangsaan Malaysia, 2024)
2024ABSTRACTSalinity has emerged as one of the agricultural plants’ most severe environmental stresses. Recently, a plant growth-promoting rhizobacteria (PGPR) is being touted as a means of solving yield and environmental issues worldwide. However, multi-strain salt-tolerant rhizobacteria have a short shelf life due to their structural and cellular components, therefore, they need to be supplemented with a liquid carrier material to serve as a shelter and energy source for the bacteria for longer survival. The present study has been undertaken to develop a liquid biofertilizer formulation from multi-strain salt-tolerant PGPR – UPMR, UPMRE6, and a mixed strain of UPMRB9 and UPMRE6 using an optimum amount of cell protectants, namely glycerol (5 mM), trehalose (10 mM), and polyvinyl pyrrolidone (PVP) at 1%. The shelf-life was assessed through measurements of optical density and bacterial biomass to determine the bacterial population and growth trend at monthly intervals. After three months of incubation, the optical density was the highest in the mixed strain treatment supplemented with trehalose with 1.3% and 2.2% increase relative to the UPMRE6 and UPMRB9, respectively, using the same cell protectants. Similarly, bacterial biomass production was the highest in the mixed strains treatment amended with trehalose (0.025 g/mL), with 13.64% and 38.89% increment followed by UPMRE6 and UPMRB9, respectively. Irrespective of the type of protectants used and PGPR type, the optical density and bacterial biomass generally decreased long incubation period. The results demonstrated that the use of 10 mM trehalose has the potential to extend the bacterial shelf life with the slightest cell loss.